2020
DOI: 10.1101/2020.02.26.20028225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical features and sexual transmission potential of SARS-CoV-2 infected female patients: a descriptive study in Wuhan, China

Abstract: Background: As of March 2, 2020, SARS-CoV-2 has infected more than 80174 people and caused 2915 deaths in China. This virus rapidly spreads to 56 countries worldwide. Thus, in order to effectively block its transmission, it is urgent to uncover all the possible transmission routes of SARS-CoV-2. Methods: From January 28 to February 18, 2020, 35 female patients diagnosed with COVID-19 in Tongji Hospital were included in this descriptive study. The gynecologic history, clinical characteristics, laboratory findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
5
32
0
2
Order By: Relevance
“…We conclude that a subset of trophoblast cells may be permissive to SARS-CoV-2 entry. Overall, our findings for the placenta are consistent with current clinical data suggesting that vertical transmission of SARS-CoV-2 from infected mother to fetus is plausible, but probably rare (Baud et al, 2020;Chen et al, 2020a;Cui et al, 2020;Hosier et al, 2020;Zeng et al, 2020). Future studies should be directed at examining SCARF expression at different .…”
Section: The Developing Embryo May Be At Risk Of Infectionsupporting
confidence: 89%
“…We conclude that a subset of trophoblast cells may be permissive to SARS-CoV-2 entry. Overall, our findings for the placenta are consistent with current clinical data suggesting that vertical transmission of SARS-CoV-2 from infected mother to fetus is plausible, but probably rare (Baud et al, 2020;Chen et al, 2020a;Cui et al, 2020;Hosier et al, 2020;Zeng et al, 2020). Future studies should be directed at examining SCARF expression at different .…”
Section: The Developing Embryo May Be At Risk Of Infectionsupporting
confidence: 89%
“…Among COVID-19 patients, there are more men than women [1]. Although recent reports found no evidence of either sexual or vertical transmission by women infected with the 2019-nCoV [4,5], very little is known about the potential impact of 2019-nCoV infection on the male reproductive system. Of interest, bioinformatic analyses have revealed that angiotensin-converting enzyme 2, a receptor utilized by the 2019-nCoV, is abundantly expressed in the testis and male reproductive tract [6,7], raising an urgent question of potential sexual transmission through semen by men.…”
Section: Dear Editormentioning
confidence: 99%
“…Recently, two studies have answered whether 2019-nCoV could spread sexually or vertically and pose risks to the fetus and neonate among female patients [7,8]. No evidence was showed for sexual transmission or intrauterine infection caused by vertical transmission in women who develop COVID-19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%